A Cell Electrofusion Chip for Somatic Cells Reprogramming - Wu, Wei (PLoS One, 2015)
Cell fusion is a potent approach to explore the mechanisms of somatic cells reprogramming. However, previous fusion methods, such as polyethylene glycol (PEG) mediated cell fusion, are often limited by poor fusion yields. In this study, we developed a simplified cell electrofusion chip, which was based on a micro-cavity/ discrete microelectrode structure to improve the fusion efficiency and to reduce multi-cell electrofusion. Using this chip, we could efficiently fuse NIH3T3 cells and mouse embryonic stem cells (mESCs) to induce somatic cells reprogramming. We also found that fused cells demethylated gradually and 5-hydroxymethylcytosine (5hmC) was involved in the demethylation during the reprogramming. Thus, the cell electrofusion chip would facilitate reprogramming mechanisms research by improving efficiency of cell fusion and reducing workloads.